The Use of Solar Radiation in Agricultural Processing - S. P. Chow; Allen C. Brailey (Institute for Research and Community Services (LPPM) ITB, 1977)
Abstract. Recent solar radiation data in different parts of Malaysia indicates that Malaysia has an abundant energy resource that could be tapped and used for agricultural processing. A brief survey on the potential uses of this solar energy is given and mention is made of the types of application, the products and processes involved. Examples for Malaysian agricultural products are used. Ringkasan. Data terakhir mengenai radiasi matahari di beberapa tempat yang berbeda-beda di Malaysia memberikan indikasi bahwa Malaysia memiliki sumber enersi yang berlebihan yang dapat digunakan untuk pengolahan hasil-hasil pertanian. Suatu penelaahan mengenai potensi penggunakan enersi matahari diberikan secara singkat dan disebutkan pula beberapa jenis penggunaan, macam hasil olahan dan cara pengolahan yang terlibat. Beberapa hasil pertanian Malaysia digunakan sebagai contoh.